2012
DOI: 10.1186/1471-2164-13-272
|View full text |Cite
|
Sign up to set email alerts
|

Losing identity: structural diversity of transposable elements belonging to different classes in the genome of Anopheles gambiae

Abstract: BackgroundTransposable elements (TEs), both DNA transposons and retrotransposons, are genetic elements with the main characteristic of being able to mobilize and amplify their own representation within genomes, utilizing different mechanisms of transposition. An almost universal feature of TEs in eukaryotic genomes is their inability to transpose by themselves, mainly as the result of sequence degeneration (by either mutations or deletions). Most of the elements are thus either inactive or non-autonomous. Cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 74 publications
0
34
0
Order By: Relevance
“…Trees generated using internal coding sequences also displayed the same general topology (S3 Fig. ), but offered less phylogenetic resolution due to the more constrained nature of retroviral coding sequences relative to LTRs [72,73].…”
Section: Resultsmentioning
confidence: 99%
“…Trees generated using internal coding sequences also displayed the same general topology (S3 Fig. ), but offered less phylogenetic resolution due to the more constrained nature of retroviral coding sequences relative to LTRs [72,73].…”
Section: Resultsmentioning
confidence: 99%
“…To further classify MLERVs into subfamilies, we compared their LTR sequences, which are among the most rapidly evolving sequences in retroviruses (49,50). Based on a 75% interelement LTR nucleotide similarity cutoff, the program Vmatch (www .vmatch.de) clustered the 362 potential complete ERVs into 86 subfamilies (including 40 singletons) (see Table S2 in the supplemental material).…”
Section: De Novo Detection Of Ervs In the M Lucifugus Genomementioning
confidence: 99%
“…Studies examining scattered repetitive elements in insect genomes have also shown that after the invasion phase, they tend to be silenced and subsequently undergo molecular deterioration until incorporation into the host genome [Fernán-dez-Medina et al, 2012]. In the molecular deterioration phase, the element becomes inactive and progressively accumulates mutations, insertions and deletions at neutral rates until it completely loses its identity or is lost in the host genome [Fernández-Medina et al, 2012].…”
Section: Chromosomal Distribution Of Repetitive Sequences On Autosomesmentioning
confidence: 99%